2021
DOI: 10.3390/ijms22168926
|View full text |Cite
|
Sign up to set email alerts
|

17,20S(OH)2pD Can Prevent the Development of Skin Fibrosis in the Bleomycin-Induced Scleroderma Mouse Model

Abstract: Systemic sclerosis (SSc; scleroderma) is a chronic fibrotic disease involving TGF-β1. Low serum vitamin D (vit D) correlates with the degree of fibrosis and expression of TGF-β1. This study was designed to determine whether the noncalcemic vit D analog, 17,20S(OH)2pD, suppresses fibrosis and mediators of the TGF-β1 pathway in the bleomycin (BLM) model of fibrosis. Fibrosis was induced into the skin of female C57BL/6 mice by repeated injections of BLM (50 μg/100 μL) subcutaneously. Mice received daily oral gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…We have discovered several CYP11A1-derived vitamin D3 hydroxymetabolites, some of which are naturally found in human serum [72,73], in human organs or cells [13,14] and in bees' honey [74], with metabolites lacking a hydroxyl group on C1α being non-calcemic [24,25]. We previously reported that these vitamin D3 hydroxymetabolites, similarly to 1,25(OH) 2 D3 [52], have the ability to reduce fibrosis in human cells [22,23] or murine skin in vivo [17,53]. In mice, this effect required the expression of the RORγ receptor [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have discovered several CYP11A1-derived vitamin D3 hydroxymetabolites, some of which are naturally found in human serum [72,73], in human organs or cells [13,14] and in bees' honey [74], with metabolites lacking a hydroxyl group on C1α being non-calcemic [24,25]. We previously reported that these vitamin D3 hydroxymetabolites, similarly to 1,25(OH) 2 D3 [52], have the ability to reduce fibrosis in human cells [22,23] or murine skin in vivo [17,53]. In mice, this effect required the expression of the RORγ receptor [55].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies have demonstrated the inhibitory effect of 1,25(OH) 2 D3 in fibrotic skin diseases [28,44,48,49,51,52]. In addition, several D3 metabolites have been tested on fibroblasts, including 20(OH)D3 and 20,23(OH) 2 D3, the major products of CYP11A1-mediated vitamin D3 metabolism [17,23,53,54]. Both metabolites suppress fibrogenesis and cell proliferation, as tested on murine skin and human skin cells [17,23,55].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these data, the anti-fibrogenic activity of vitamin D has been reported in murine models of scleroderma. Specifically, in mice with bleomycin-induced skin fibrosis, the treatment with systemic topical vitamin D analogs reduced the amount of fibrosis [ 27 , 28 , 29 , 30 ] by down-regulating TGF-β signalling and by modulating cytokine mediators, such as IL-13, TNF-α, IL-6, IL-17, and IL-12p70 [ 34 ]. These findings suggest that the effect of vitamin D in this context is in part directly related to its activity on crucial pathways of fibrosis development and in part to the modulation of the immune system; indeed, in blood samples collected from SSc patients, vitamin D supplementation increased IL-10 production by T-reg lymphocytes providing a “suppressive” cytokine milieu able to modulate immune response [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…CYP11A1-derived secosteroids can inhibit proliferation of human keratinocytes and melanocytes [61][62][63][64], stimulate cell differentiation [259,260], decrease inflammation [249,250,260] and prevent pathological skin fibrosis [261,262] similarly to 1,25(OH) 2 D3 (Figure 2). However, they can act through different receptors.…”
Section: Mechanism Of Action Of Novel Vitamin D Hydroxyderivatives As...mentioning
confidence: 99%